Social Dimensions of Climate Change : Equity and Vulnerability in a Warming World - Mearns, Robin (World Bank, 2012)
Climate change is widely acknowledged as foremost among the formidable challenges facing the international community in the 21st century. It poses challenges to fundamental elements of our understanding of appropriate goals for social and economic policy, such as the connection of prosperity, growth, equity, and sustainable development. This volume seeks to establish an agenda for research and action built on an enhanced understanding of the relationship between climate change and the key social dimensions of vulnerability, social justice, and equity. The volume is organized as follows. This introductory chapter first sets the scene by framing climate change as an issue of social justice at multiple levels, and by highlighting equity and vulnerability as the central organizing themes of an agenda on the social dimensions of climate change. Chapter two leads off with a review of existing theories and frameworks for understanding vulnerability, drawing out implications for pro-poor climate policy. Understanding the multilayered causal structure of vulnerability then can assist in identifying entry points for pro-poor climate policy at multiple levels. Building on such analytical approaches, chapters three and four, respectively, consider the implications of climate change for armed conflict and for migration. Those chapters are followed by a discussion of two of the most important social cleavages that characterize distinct forms of vulnerability to climate change and climate action: gender (chapter five) and ethnicity or indigenous identity (chapter six), in the latter case, focusing on the role of indigenous knowledge in crafting climate response measures in the Latin American and Caribbean region. Chapter seven highlights the important mediating role of local institutions in achieving more equitable, pro-poor outcomes from efforts to support adaptation to climate change. Chapter eight examines the implications of climate change for agrarian societies living in dry-land areas of the developing world, and chapter nine does the same for those living in urban centers. Chapter ten considers the role of social policy instruments in supporting pro-poor adaptation to climate change; and it argues for a focus on 'no-regrets' options that integrate adaptation with existing development approaches, albeit with modifications to take better account of the ways in which climate variables interact with other drivers of vulnerability. Finally, chapter eleven turns to the implications of climate policy and action for forest areas and forest people.